Fear of Disconnection in Adolescents – FOMO Prevention in the School Environment - Pietryga-Szkarłat, Barbara; Curyło-Sikora, Patrycja (INSTED: Interdisciplinary Studies in Education & Society, 2024)
Living in a constantly evolving world where access to new technologies is common requires reflection on the benefits and threats of their use. One of such threats is the phenomenon of FOMO (fear of missing out), which is becoming more and more common in the modern world. It is associated with experiencing fear due to the inability to participate in spaces where electronic communication takes place. The phenomenon of FOMO is a relatively new risky behavior that has appeared due to the popularization of social media and mobile devices. This syndrome affects the holistic functioning of a person - it affects his cognitive, emotional, social and physical spheres, and is based on psychosocial factors. Therefore, there is a need to recognize it as a social problem and take early, systemic and long-term actions for students and their parents, aimed at increasing awareness of the issue in question and the involvement of teachers and specialists (including doctors) in this process.